2021
DOI: 10.3168/jds.2020-18729
|View full text |Cite
|
Sign up to set email alerts
|

Identification of biomarkers measured upon arrival associated with morbidity, mortality, and average daily gain in grain-fed veal calves

Abstract: There is a strong need for management strategies that help reduce the incidence of disease and subsequent antimicrobial use in the veal industry. Biomarkers could serve as useful tools that allow producers to take preventative measures before clinical problems occur. The objective of this prospective cohort study was to identify biomarkers measured upon arrival associated with morbidity, mortality, and average daily gain (ADG) in grain-fed veal calves. Upon arrival at a grain-fed veal facility in Ontario, Cana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 51 publications
1
26
0
Order By: Relevance
“…Given the multiple challenges from birth to arrival at calf-raisers (Figure 1), the first few weeks at the calf-raiser are a high-risk period. Over an 11 week period at a calf raiser in Ontario, 7.5% of calves died and almost 90% were treated with antimicrobials at least once for disease (27,40). Scott et al (27) and Renaud et al (2) also found 68% of calves were treated with antibiotics and 42% of calf deaths, respectively, occurred within the first 3 weeks after arrival to calf raisers.…”
Section: Calf Healthmentioning
confidence: 99%
See 3 more Smart Citations
“…Given the multiple challenges from birth to arrival at calf-raisers (Figure 1), the first few weeks at the calf-raiser are a high-risk period. Over an 11 week period at a calf raiser in Ontario, 7.5% of calves died and almost 90% were treated with antimicrobials at least once for disease (27,40). Scott et al (27) and Renaud et al (2) also found 68% of calves were treated with antibiotics and 42% of calf deaths, respectively, occurred within the first 3 weeks after arrival to calf raisers.…”
Section: Calf Healthmentioning
confidence: 99%
“…Current antimicrobials use rates are influenced by high disease susceptibility and prevalent health abnormalities. For example, almost 90% of calves raised at a grain-fed veal facility in Ontario were treated with antimicrobials at least once during an 11week period (27,40). High rates of antimicrobial use has been associated with the development of antimicrobial resistance in commensal and pathogenic bacteria within the digestive and respiratory tract of veal calves (41,42) and increased carriage of antimicrobial resistant bacteria in calf caretakers (43).…”
Section: Antimicrobial Usagementioning
confidence: 99%
See 2 more Smart Citations
“…Recent observational studies have found associations between the background and rearing practices at the dairy farm of origin and mortality rate of calves at the veal farm (Winder et al, 2016;Renaud et al, 2018a). Correspondingly, BW and the clinical health condition of calves upon arrival at the veal farm (Renaud et al, 2018b;Scott et al, 2019) as well as biomarkers analyzed in a blood sample taken at arrival, including immunoglobulins (Pardon et al, 2015;Goetz et al, 2021), cholesterol (Renaud et al, 2018b), or specific immune cell counts (von Konigslow et al, 2020), were all significantly correlated with later risks of disease and mortality. Collectively, these studies suggest that both transport and husbandry characteristics at the dairy farm of origin may be important determinants of the biological state of a calf when it arrives at the veal farm.…”
Section: Introductionmentioning
confidence: 95%